Das Verhalten einer ganzen transzendenten Funktion bei grossen Werten ihres absoluten Betrages - Strelits, S. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. И. Стрелиц. Поведение целой трансцендентной функции многих комплексных переменных при больших значениях её модуляŠ. Strelicas. Daugelio kintamųjų sveikos transcendentinės funkcijos elgimasis, esant didelėms jos modulio reikšmėms